Model Pembelajaran dan Tingkat Kecerdasan Anak (Studi Pembelajaran Tahfidz di MI Al-Kautsar) - Umi Kalsum (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
This article looks at the use of the Al-Qur'an memorization method at MI Al-Kautsar Ponorogo. The purpose of this study was used to analyze how the method of memorizing the Al-Qur'an at MI Al-Kautsar Ponorogo was selected at the level of child intelligence. Therefore, to analyze it with field analysis and use a theoretical approach to child intelligence. From the results of the reading, it can be concluded: first, the sima'i method is by the ability to memorize the Al-Qur'an in low-grade children who still need more concentration. Where the teacher reads the verses, that will be memorized slowly and the child follows the reading, and so on. so that the child can memorize the letters in the Qur'an. Second, the use of the tallaqi method or technique is by the abilities of high-class children, where the ability and readiness to concentrate are more prepared and have a good memory. This is evidenced by the number of memorizations tends to be more.